Strategic Planning’s Impact on Organizational Effectiveness Via Human Resource Investment: A Study on Iraq’s National Investment Commission Employees - Ahmed, Inas Yadallah; Dellagi, Hatem; Abdulameer, Lebanon Hatif; Mohammad, Suleiman Ibrahim; Vasudevan, Asokan (Journal of Posthumanism, 2025)
The study aimed to elucidate the impact of strategic planning on enhancing organizational effectiveness through the investment in human resources as a mediating variable. This empirical research was conducted among employees of the National Investment Authority in Iraq. A descriptive analytical methodology was employed, with the study population comprising 3,022 employees in senior and middle management positions. Among these, 490 held senior roles, while 2,532 occupied middle management positions. A stratified sampling technique was utilized, resulting in a final sample of 352 respondents, representing 11.46% of the valid questionnaires for statistical analysis. A questionnaire was developed as a data collection tool, and the study utilized the Statistical Package for the Social Sciences (SPSS V.24) and the AMOS program for path analysis. Various descriptive and inferential statistical methods were applied. The findings indicated that the respondents’ perceptions of the application of strategic planning—encompassing dimensions such as strategic vision, strategic mission, strategic objectives, strategic analysis, and strategic options—alongside the level of organizational effectiveness, were rated as moderate. In contrast, the level of investment in human resources was found to be high.